2020
DOI: 10.1007/s11104-020-04525-0
|View full text |Cite
|
Sign up to set email alerts
|

Root xylem in three woody angiosperm species is not more vulnerable to embolism than stem xylem

Abstract: Aims Since plants are compartmentalised organisms, failure of their hydraulic transport system could differ between organs. We test here whether xylem tissue of stems and roots differ in their drought-induced embolism resistance, and whether intact roots are equally resistant to embolism than root segments. Methods Embolism resistance of stem and root xylem was measured based on the pneumatic technique for Acer campestre, A. pseudoplatanus and Corylus avellana, comparing also intact roots and root segments of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 88 publications
0
25
0
Order By: Relevance
“…We need to acknowledge that a limitation of this study was the use of stem PLC as a proxy for root PLC. Previous studies have indicated how this proxy can be problematic when there is substantial hydraulic segmentation (Johnson et al, 2016) because roots have sometimes (Tyree & Zimmerman, 2002), but not always (Wu et al, 2020), been documented to be more vulnerable to embolism than stems. Although the existence of hydraulic segmentation was formulated long ago (Zimmermann, 1978), it is still unclear how prevalent it is across species (Wu et al, 2020).…”
Section: Limitations On the Use Of Stem Plc As A Proxy For Root Plcmentioning
confidence: 99%
“…We need to acknowledge that a limitation of this study was the use of stem PLC as a proxy for root PLC. Previous studies have indicated how this proxy can be problematic when there is substantial hydraulic segmentation (Johnson et al, 2016) because roots have sometimes (Tyree & Zimmerman, 2002), but not always (Wu et al, 2020), been documented to be more vulnerable to embolism than stems. Although the existence of hydraulic segmentation was formulated long ago (Zimmermann, 1978), it is still unclear how prevalent it is across species (Wu et al, 2020).…”
Section: Limitations On the Use Of Stem Plc As A Proxy For Root Plcmentioning
confidence: 99%
“…Yet, large and wide vessels are likely to embolise first, and this temporal difference could be caused by their connectivity to a gas source, and may not reflect any inherent difference in embolism resistance per se. No alternative mechanism is known why wide conduits would be vulnerable to embolism, since pit membrane thickness, which is strongly associated with embolism resistance (Li et al , 2016), was not related to conduit diameter (Kotowska et al , 2020;Wu et al , 2020).…”
Section: Embolism Spreading Depends On Pre-existing Embolism As Gas Smentioning
confidence: 99%
“…These observations may give the impression that wide conduits are more vulnerable to embolism, although any functional explanation for such differential embolism resistance remains unclear. Indeed, pit membrane thickness, which is a major determinant of vulnerability to embolism (Li et al , 2016;Kaack et al , 2019), is not related to conduit dimensions (Klepsch et al , 2018;Wu et al , 2020;Kotowska et al , 2020). If the proximity of a gas source would determine embolism spreading, we expect that narrow and short vessels near cut minor veins would embolise before embolism occurs in the large vessels of major veins, which would make narrow vessels seemingly more vulnerable than wide ones.…”
Section: Introductionmentioning
confidence: 98%
“…xylem (Pereira et al 2020), we present a semi-automated method to measure VLD using the Pneumatron. This instrument is based on the Pneumatic method (Pereira et al 2016;Bittencourt et al 2018;Jansen et al 2020), which measures the amount of gas that can be extracted from stems (Pereira et al 2016;Zhang et al 2018), roots (Wu et al 2020), or leaves (Pereira et al 2020). By measuring pressure changes inside a fixed tube volume over time, gas conductivity is calculated by extracting gas from plant xylem under subatmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%